Factors associated with cut injuries among restaurant workers- a systematic review - Dapari, Rahmat; Md Yid, Mohd Faheem; Nagaraju, Aasha; Mohamad, Khairul Nadzry; Adnan, Siti Raihan; Hassan, Mohd Rohaizat; Che Dom, Nazri; Syed Abdul Rahim, Syed Sharizman (Malaysian Public Health Physicians Association, 2024)
The global food service market is projected to grow from USD$2,540.05 billion in 2022 to USD$5,194.60 billion by 2029, a Compound Annual Growth Rate (CAGR) of 10.76% in the forecast period. Because the industry is highly lucrative, it is critical to understand the prevalence and risk factors of work-related injuries among workers in this sector to implement safe working conditions and reduce costs associated with workplace injuries. However, it has been reported that restaurant or kitchen workers have high risks of work-related disease and injuries. In the United States, occupational injuries were estimated to cost the industry approximately USD$250 billion in 2010, which were largely contributed by food production and food preparation industries(Forum, 2009). In this study, potential associated factors are job demands, physical stress and psychological stress. This systematic review aims to present and systematically determine the factors associated with cut injuries among restaurant workers. Articles related to factors associated with cut injuries among restaurant workers were collected electronically from three different databases (Medline, ScienceDirect and SpringerLink). Two pairs of independent reviewers screened the titles and abstracts of the collected data, stored in Microsoft Excel Version 16.68 against the inclusion and exclusion criteria. Afterwards, the included articles were critically appraised to assess the quality of the studies using the Mixed Method Appraisal Tool (MMAT). Of the 13 articles identified, four reports were included in the final review. The non-modifiable factors (gender and age) and modifiable factors (years of working experience, workplace environment and work description) are associated with cut injuries among restaurant workers. To reduce cut injuries among restaurant workers, safety and hazard reduction programs can be developed by tailoring it according to modifiable factors and non-modifiable factors.